Schattenkinder . Children in the Shadow - Haertel, Caroline; Momirovic, Mirjana (Germany, 2006)
Verzio FF submission Many films have already attempted to portray what it is like to raise children with disabilities – from the parents’ perspective. But what is it like to grow up as the brother or sister of a disabled child? Always a slightly in the background, slightly in the shadow. This film pioneers this approach by presenting the lives of three "shadow" children. Three different children, three different stories with one common feature: their childhood spent in the shadow.